Preserving the functional asymmetry of the muscular system in young hockey players through compensatory exercises - Mironov A.O.; Spiridonov E.A.; Khutin S.A.; Ponimasov O.E. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the legal implications of incorporating the metaverse into the world of sports. Methods and structure of the study. The fundamental approach to this research is the experimental method. The researchers employed specialized equipment, including a virtual reality headset (MetaOculusQuest – 2), to fully immerse themselves in the realm of virtual reality. This allowed them to recreate a boxing simulation that closely resembled the real thing. Results and conclusions. The creation of immersive virtual reality simulations of individual sports events demands a substantial mental and physical investment from the user, akin to the effort required for real-world sports. Given the metaverse’s potential to encompass numerous virtual worlds, it is reasonable to anticipate that one of these will be dedicated to the realm of sports. The primary legal challenges in integrating the metaverse into the sports industry revolve around issues of identity verification and cheating.